From theory to hands-on: teaching experimental plasma physics using small plasma devices at DTU. (1st November 2022) - Rasmussen, Jesper; Grulke, Olaf; Nielsen, Stefan Kragh
Abstract: At the Technical University of Denmark (DTU), we have in recent years acquired or developed three small plasma devices. These consist of a small tokamak (NORTH), an inertial electrostatic confinement device, and a linear plasma device. This has enabled a restructuring of our teaching in plasma physics and nuclear fusion, allowing courses with a dedicated experimental focus. Here we describe the use of these devices in our teaching of fusion plasma physics, with particular emphasis on their integration in a new experimental Master's level course. We also present examples of BSc and MSc projects completed at these experiments and offer some didactic reflections on student learning during our courses and projects. Our experience so far has validated the potential for student-driven activities at all levels to make useful scientific contributions to the experimental study of laboratory plasmas.